The malleable and projective nature of Peruvian caricature during the 1992 coup d’état - Infante Yupanqui, Carlos (2020)
The following article presents the results of the study on the role of graphic humor in Peru in the face of the 1992 coup d'état. We examined a significant number of caricatures from a historical, critical and contextual approach. The idea was continue following the path of Peruvian caricature. The results of the study showed that the caricature ratifies its projective, complex, and malleable condition. It did not play a key role in creating the conditions for the coup but it certainly served to that purpose. It was an excellent vehicle to penetrate the social imaginaries. It achieved its goal by asserting itself in the common sense of Peruvian society, becoming the magma of imaginary representations, from where it would nurture humor with new and old symbolic elements. In the study, we applied a qualitative methodological approach. The analysis followed the symbolic interactionism perspective.